Cellulose nanocrystals: mind the microgap in iridescent Cellulose Nanocrystal Films - Fernandes, Susete N. (2018)
Solid films prepared from cellulose nanocrystals (CNCs) present remarkable optical properties: iridescence,[1] selective reflection of left circularly polarized (LCP) light, and transmission of right circularly polarized (RCP) light.[2] The same phenomenon has been observed in certain insect cuticles, for example in the Plusiotis batesi as well as in the Plusiotis optima, where only LCP light is selectively reflected by the cholesteric structure forming the outer exocuticle.[3] In cellulosic films, the adopted left-handed chiral structure is attributed to the self-assembly of nanorods from chiral cellulose.[4] The value of the wavelength of the reflected structure (λ) depends upon the pitch (P) and the average refraction index (n) of the material according to the de Vries expression: